OPTIMIZATION OF SOCIAL SUPPORT EXPENDITURES WITHIN THE STATE BUDGET EXPENDITURES - Scientific Advisor: M. Sharapova; Isaxonova Ruxshona (Journals Park Publishing, 2024)
In this article, issues related to financing the needs of the population for social support from the state budget funds have been highlighted and analyzed. Also, attention has been paid to optimizing the costs of social support in the composition of state budget expenditures.
Keywords: social support, social protection, social assistance, social welfare, state budget, budget expenditures, “Temir daftar”, “Ayollar daftari”(“Women’s register”), “Yoshlar daftari”(“Youth register”).